Free flap and kickstand external fixator in foot and ankle soft tissue reconstruction. The versatility of a microsurgical-friendly application of an orthopedic device. (November 2018) - Maruccia, M.; Elia, R.; Caizzi, G.; Carrozzo, M.; Vicenti, G.; Moretti, B.; Giudice, G.
Abstract: Introduction: Foot and ankle are prone to injuries and often require free flap for complex soft tissue reconstruction due to the insufficiency of local soft tissue. Lower limb reconstruction can be commonly compromised by venous insufficiency, and the elevation of the limb represents a critical component of the postoperative care. This study aims to explore the versatility of combining free soft tissue flap reconstruction for complex foot and ankle defect with a temporary Kickstands External Fixator (KEF) placement. Materials and methods: A retrospective analysis was performed on 14 patients with unilateral foot or ankle complex soft tissue defects (post-traumatic, soft tissue infection and osteomyelitis, chronic skin ulcer, sarcoma), treated with free flap and KEF placement. Patients' demographics, etiology of injury, type of reconstruction, duration of KEF, complications related to the flap and the KEF placement were recorded. Results: The mean age of patients was 52.57-year-old (range 35–68). The average follow up was 15.5 months (range: 3–25). An anterolateral thigh (ALT) flap was performed in 12 patients; 2 patients received composite forearm free flap plus flexor carpalis radial for Achilles tendon reconstruction. The average time for KEF removal was 378 weeks. All flaps survived, though partial necrosis was observed in 1 case. No complication at the flap donor site or related to the KEF placement was observed. No equinus deformity was reported. Conclusion: The KEF placement when performing a complex soft tissue free flap reconstruction of foot and ankle could be an effective method to guarantee limb elevation, avoid pressure on the flap especially in posterior reconstructions, avoid heel pressure ulcer formation and equinus deformity.